Opposition to the British Government's "recognition of the Spanish insurgent authorities" (draft statement)
017b-0016-001 Issued by the National Council of Labour, February 14, 1939. House of Commons. A special meeting of the National Council of Labour was held today (Tuesday) to consider the latest developments in Spain. It was reported to the Council that Mr Attlee had put the following Private Notice Question to the Prime Minister: "whether, in view of the important issues involved, any decision, conditional or otherwise, to recognise the Spanish insurgent authorities as the defacto or de jure Government of Spain will be communicated to this House before any action is taken thereon, with a view to an early Debate?" The Prime Minister's reply intimating that the Government would naturally communicate to the House at the earliest possible moment any decision at which it might feel it necessary to arrive, but giving giving no assurance that the House could debate the question before any action was taken, gave the National Council of Labour grave dissatisfaction. The Council expressed its profound opposition to the recognition of the Spanish insurgent authorities whilst the legitimate Government of Spain continue to function, such recognition being in the Council's view contrary to public law and against the wishes of the great mass of British public opinion. 292/946/17b/16